Virtsarakon EWSR1::BEND2 -fuusiosarkooma - tapausselostus - Halava, Vili (My University, 2025)
The variety of EWSR1 rearranged tumors is expanding and the relevance of traditional method for detecting Ewing sarcoma with fluorescence in situ hybridization is decreasing. With modern tumor agnostic methods, mainly next generation sequencing, NGS, novel fusions are being found at an accelerating rate. The classification of these tumors into WHO defined entities to guide treatment is a challenge. In this report we describe a 28-year-old male patient who was diagnosed with a Ewing-like high grade small round cell sarcoma at the time of diagnosis. Later, RNA sequencing revealed an extremely rare EWSR1::BEND2 fusion. A large necrotic tumor with multiple lung metastasis and spreading to adjacent prostatic tissue was seen at the time of diagnosis. The tumor is an undifferentiated small round cell tumor with perivascular rosette formation and moderate CD99 membranous positivity. The methylation profile of the tumor did not match with any of the tumor entities grouped by the sarcoma classifier. The original diagnosis of an extraskeletal Ewing sarcoma was justified at the time as modern molecular techniques were not available. Our case adds to the ever-expanding group of neoplasms known as EWSR1-non-ETS fusion sarcomas, and describes the effects of a commonly used cytostatic protocol on this type of sarcoma.
Keywords: fusion sarcoma, EWSR1::BEND2, undifferentiated small round cell sarcoma, Ewing-like sarcoma